Factors Influencing People's Decisions to Use Islamic Bank Products - maimuna maimuna; Windari windari; muhammad isa; rahmat anam (Journal Of Sharia Banking, 2020)
This research is motivated by the habits of the people who use conventional banks and the small number of people in Batu Hula Village, Batangtoru District who use Islamic banks. This is caused by several factors that influence people's decisions, including cultural factors, social factors, and personal factors. Based on the results of the research, the cultural factor variable partially has a significant effect on people's decisions, this is evidenced in the results of hypothesis testing that the cultural factor variable has tcount ttable (3,932 1,69726), then H0 is rejected and Ha is accepted. on community decisions, this is proven by the results of hypothesis testing that the social factor variable has tcount ttable (1,726 1,69726), then Haditolak and H0 are accepted. And the personal factor variable partially has no effect on people's decisions, this is evidenced by hypothesis testing that the cultural factor variable has tcount ttable (0,188 21,69726). Then the variables of cultural factors, social factors and personal factors variables simultaneously affect people's decisions with the results Fcount Ftable (23,362 2,28).